2015
DOI: 10.1175/jcli-d-14-00599.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Localized Grid Refinement on the General Circulation and Climatology in the Community Atmosphere Model

Abstract: Using the spectral element (SE) dynamical core within the National Center for Atmospheric Research-Department of Energy Community Atmosphere Model (CAM), a regionally refined nest at 0.258 (;28 km) horizontal resolution located over the North Atlantic is embedded within a global 18 (;111 km) grid. A 23-yr simulation using Atmospheric Model Intercomparison Project (AMIP) protocols and default CAM, version 5, physics is compared to an identically forced run using the global 18 (;111 km) grid without refinement. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
69
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 80 publications
2
69
0
Order By: Relevance
“…In particular, simulations at 0.125 ($14 km) conducted in Huang et al [2016] did not show a statistically significant change in temperature statistics over California. In our study, as in Zarzycki et al [2015], general circulation patterns (e.g., wind, pressure and precipitation) do not exhibit apparent artifacts in the variable-resolution transition region. A detailed description of the techniques of VR-CESM employed in this paper can be found in Rhoades et al [2015].…”
Section: Introductionsupporting
confidence: 76%
“…In particular, simulations at 0.125 ($14 km) conducted in Huang et al [2016] did not show a statistically significant change in temperature statistics over California. In our study, as in Zarzycki et al [2015], general circulation patterns (e.g., wind, pressure and precipitation) do not exhibit apparent artifacts in the variable-resolution transition region. A detailed description of the techniques of VR-CESM employed in this paper can be found in Rhoades et al [2015].…”
Section: Introductionsupporting
confidence: 76%
“…With a refined high resolution, VR-CESM has shown significant improvements of the Atlantic tropical storms (Zarzycki and Jablonowski, 2014) and South America orographic precipitation (Zarzycki et al, 2015). The model has also been used in the regional climate simulations over the western US, and the results show that the VR-CESM is capable of reproducing the spatial patterns and the seasonal evolution of temperature, precipitation, and snowpack in the Sierra Nevada Rhoades et al, 2016) and Rocky Mountains (Wu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Strategies that have been employed for transitioning between coarse and fine‐resolution regions within a VRGCM include grid stretching [ Fox‐Rabinovitz et al ., ; McGregor and Dix , ] and grid refinement [ Ringler et al ., ; Skamarock et al ., ; Zarzycki et al ., ]. VRGCMs have demonstrated utility for regional climate studies and applications at a reduced computational cost compared to uniform‐resolution GCMs [ Fox‐Rabinovitz et al ., ; Rauscher et al ., ; Zarzycki et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…Zarzycki et al . [] also compared the large‐scale climatology of VR‐CESM 0.25° and uniform CESM at 1° and found that adding a refined region over the globe did not noticeably affect the global circulation. Rhoades et al .…”
Section: Introductionmentioning
confidence: 99%